Role of various causes of death in diverging life expectancy in Kerala, India - A., Anjana; Chacko, Asha T. (International Journal of Research in Medical Sciences, 2023)
Background: Life expectancy at birth is an indicator of mortality conditions and health conditions. Mortality happens due to many causes. The multiple-decrement life table is used widely in human actuarial literature and provides statistical expressions for mortality in which the cause elimination is used. Cause elimination life tables address the hypothetical question of what a cohort’s mortality experience would be if a particular cause of death were eliminated. The goal of this study is to estimate the potential gain in life expectancy after complete elimination of certain causes of death in Kerala, India for the year 2018. Methods: The data for the study was taken from annual vital statistic report, Kerala, 2018. Life table method was used for estimating the potential gain in life expectancy after eliminating certain causes of deaths. Results: The elimination of deaths due to heart diseases, cancer, respiratory diseases, accidents and suicides resulted a gain of 7.18 years, 6.90 years, 8.04 years, 6.72 years and 7.09 years respectively. The results show that in 2018, for Kerala, the highest gain in life expectancy was due to elimination of respiratory diseases, followed by other causes of death. The present study shows that heart diseases and respiratory diseases are the causes which are more affected among Keralites. Conclusions: Effective intervention needs to be implemented in Kerala so as to reduce the risk of the diseases, which would result in the increase of life expectancy at birth.